THE ANTECEDENTS OF COFFEE SHOP CUSTOMERS’ SATISFACTION (A CASE STUDY ON ‘KOPI KENANGAN’ OUTLET IN WEST JAKARTA, INDONESIA) - Ruslim, Tommy Setiawan; Sukaman, John Victorino; Siswanto, Halim Putera; Saktiana, Galuh Mira (Graduate Program of Universitas Tarumanagara, 2024)
A phenomenon of the popular and rapid development in coffee shops in Indonesia has driven an increasingly fierce competition among business actors in this industry. The purpose of this research was to examine the effects of coffee quality, service quality, and perceived price on the satisfaction of ‘Kopi Kenangan’ customers in West Jakarta, Indonesia. The samples of this study were 302 customers of ‘Kopi Kenangan’ outlet at Citraland Mall in West Jakarta. Data was processed in this study using SmartPLS version 3.2.9. As the results of this research, coffee quality, service quality, and perceived price partially has a positive and significant effect on the satisfaction of ‘Kopi Kenangan’ customers at Citraland Mall outlet in West Jakarta. This finding can be expected to help business owners in formulating the ideal marketing strategies in the future.